Pengaruh Pemanfaatan Short Message Servive (SMS) terhadap Keaktifan Kader Posyandu Lanjut Usia di Desa Kriwen Kabupaten Sukoharjo - Susanti, Cherly Yulviansi Nur, Agus Sudaryanto, S.Kep., Ns., M.Kes, Faizah Betty R. A., S.Kep., M.Kes (2016)
The role of cadre in posyandu management is absolutely substansial. However, nationally drop out number of the cadres shown up to 30.8% that means the number of active cadre about 62.9%. schedule of the cadres with another activity graduallymake them ignore their own role as a posyandu cadre. One of strategy to maintaining the activeness and motivation for each cadres is by using text message reminder technology. The information deliveriy process wich is brief, clear and directly make it easier to them to feel noticeable. This study aimed to identifying the influence of text message reminder to increasing presence of cadres in posyandu activities. This study using pre-experment design method with one group pre-post test design plan. The population and samples of this study consist of 35 respondent, geriatric cadres in KriwenSukoharjo District. The text message intervention is being conducted before the posyandu schedule for 2 months. Then the data collecting after intervention. Data analyzing technic of pre-post test is using Wilcoxon statistic test. The result of Wilcoxon statistic test show p-value rate < 0.05. It means H0 is being rejected. There are differences between cadre's presence rate before and after the intervention being conducted. Therefore, it is concluded that there there is an influence between text message reminder to the activeness of geriatric posyandu cadres. The usage of text message reminder is expected to maintaining the cadres awareness on posyandu activity effectively.